Familial STAG2 germline mutation defines a new human cohesinopathy - Fernanda C. Soardi (Nature Portfolio, 2017)
Intellectual disability: mutation in cell cycle protein causes developmental disease A newly discovered developmental disease is characterized by mutations in a subunit of the cohesin protein involved in cell division. A team led by Sérgio Pena from GENE—Núcleo de Genética Médica, Brazil, and Hongtao Yu from the University of Texas Southwestern Medical Center, USA, describe a Brazilian family with five male relatives, all with intellectual deficiency, short stature, and other abnormalities. The family tree pointed toward an X-linked pattern of inheritance, so the researchers performed a network analysis of 24 genes on the X chromosome known to contribute to mental retardation. They found that all five individuals had a mutation in a gene called STAG2, which encodes a subunit of cohesin. The mutant STAG2 did not bind properly to other cohesin subunits in human cells, and patient-derived cells exhibited altered cell cycle profiles. The researchers propose calling the disease “STAG2-related X-linked intellectual deficiency”.